'Kollegah the Boss': A case study of persona, types of capital, and virtuosity in German gangsta rap. Issue 3 (October 2019) - Ahlers, Michael
Abstract: The article begins with a short history of German gangsta rap, followed by an overview of central theories and key concepts in hip-hop studies. It then focuses on a case study of a German gangsta rapper called Kollegah, who became one of Germany's most commercially successful artists of the past few years. The case study is divided into three parts: the first involves a deconstruction of both his artistic persona and his strategies of appropriating hip-hop cultures. This is followed by a closer look at two Kollegah productions, focusing on his rhyming and signifying skills. By adding a cursory qualitative media analysis of both Internet fan forums and print and television artefacts about Kollegah, very contradictory reactions can be depicted. The article is finally able to illustrate that this artist makes great use of a (typically German?) flavour of virtuosity and that he can draw from a very unique set of capital. Kollegah is viewed as representing a successful strategy of cultural appropriation and the use of different types of capital within the network of music business in its post-digital era.